Eksistensi Rapai Bubee Dalam Nilai-Nilai Budaya Lokal Di Aceh - Intan Rizki Junita Tri Utami (Yayasan Cendekia Gagayunan Indonesia, 2025)
Rapai Bubee is one of Aceh's traditional arts with high cultural and social values. However, its existence is increasingly threatened due to the lack of interest of the younger generation and the influence of globalization which shifts their attention to popular culture. This research aims to analyze the existence of Rapai Bubee in Pidie Jaya, especially in Gampong Mee Panglima Trienggadeng, and identify factors that support and hinder its preservation. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results showed that the lack of understanding of teachers, the lack of learning references, and the lack of appreciation for local arts are the main factors for the low participation of the younger generation in this traditional art. To overcome this, hands-on practice-based training was implemented at SMAN 2 Bireuen, which resulted in increased student understanding and motivation towards Rapai Bubee. The preservation of this art requires a comprehensive approach through education, digitization, active role of the art community, as well as government policy support. Therefore, the integration of traditional arts in the school curriculum and innovation in the packaging of art performances are strategic steps in maintaining the sustainability of Rapai Bubee amid the challenges of the modern era.